Abdominal obesity is an independent risk factor for increased carotid intima- media thickness in obese children - Hacihamdioğlu, Bülent; Okutan, Vedat; Yozgat, Yilmaz; Yildirim, Düzgün; Kocaoğlu, Murat; Lenk, Mustafa Koray; Ozcan, Okan (The Turkish Journal of Pediatrics, 2011)
We aimed in this study to investigate carotid intima-media thickness (IMT) in obese children and evaluate the relationship of IMT to various cardiovascular risk factors. One-hundred four obese children (9.3 +/- 2.5 years) and 30 healthy age-matched control subjects were enrolled in the study. All children were assessed for fasting levels of glucose, insulin, lipid profile, skinfold thickness (SFT), waist circumference (WC), and blood pressure (BP). Insulin resistance was estimated by the homeostasis model assessment (HOMA) index. Carotid IMT measurements and non-alcoholic fatty liver disease (NAFLD) were diagnosed with ultrasonographic findings. IMT was significantly higher in obese children compared to controls (0.49 +/- 0.05 vs. 0.40 +/- 0.02 mm, p < 0.001). Significant positive correlations were found between increased carotid IMT and body fat percentage (BFP), body mass index (BMI), age, height, systolic BP, WC, SFT, triglyceride and insulin levels, and insulin resistance index. In a linear logistic regression analysis, the only parameter affecting the increase in carotid IMT was WC (beta: 0.589, p < 0.001). Furthermore, IMT was increased significantly in obese children with NAFLD when compared to obese children without NAFLD (0.54 +/- 0.04 vs. 0.48 +/- 0.05 mm, p < 0.001). Children with abdominal obesity are at increased risk for atherosclerosis, and WC can be used to determine the atherosclerosis risk in obese children.